Metabolic Responses and Oxidative Stress Adaptation Mechanisms of the Pituitary Gland in the Tiger Puffer Under Low-Temperature Stress - Yifan Li; Taicheng Li; Meihui Yao; Chuan Li; Zibin Jiang; Hongyu Pan; Wei Wang; Yajuan Li; He Zhou (Fishes, 2025)
To explore the induction of low temperature the Tiger Puffer (Takifugu rubripes) In this study, the influence of temperature on the pituitary gland during masculinization was investigated through chronic hypothermia stress experiments. Metabolomics was used to analyze the metabolic regulatory network of the pituitary gland under hypothermia stress. ELISA technology was employed to determine the activity content of oxidative stress-related enzymes in the pituitary gland. Further, TUNEL fluorescence labeling and qPCR were used to detect the apoptosis level of pituitary cells. Finally, to assess the impact of low-temperature stress on muscle tissue, HE staining and qPCR techniques were employed. The results showed that after 45 days of low-temperature stress, the differential metabolites of the pituitary gland were mainly enriched in the amino acid metabolic signaling pathway, and the contents of amino acids such as GSH and its synthetic precursors in the pituitary tissue changed significantly. The contents of oxidative stress indicators such as ROS and MDA all showed a trend of first increasing and then decreasing. The qPCR results of TUNEL fluorescence labeling and apoptosis-related genes were consistent, indicating that the apoptotic level of pituitary cells first increased and then decreased with the stress process. Histological analysis revealed that low temperature led to muscle cell atrophy and increased interstitial space in muscle tissue. The expression changes in genes related to muscle development further confirmed that low temperature significantly inhibited muscle growth and development. Therefore, this study speculates that after being subjected to chronic low-temperature stress, the pituitary gland of the red-finned Oriental pufferfish can alleviate the oxidative stress response of the body by strengthening the amino acid metabolic pathway, and the fish body has shown a physiological trend of gradually adapting to low-temperature stress, but the growth and development of muscles are still significantly inhibited. The results of this study can provide theoretical support for understanding the physiological adaptation mechanism of the red-finned Oriental pufferfish to low-temperature stress and lay a foundation for subsequent in-depth exploration of the pituitary response mechanism to low temperatures.